Basic psychological needs, motivation and personal and social responsibility in primary education students depending on the sex and age of the students - González Espejo, Manuela; Sánchez Alcaraz Martínez, Bernardino; Asencio, Manuel Alfonso; Hellin Martínez, Marta (Rastros Rostros, 2021)
The aim of this paper was is based on discovering the basic psychological needs, motivation and personaland social responsibility which are linked to the differences on the sex and age of students. The sample iscomposed by 50 students (26 boys and 24 girls) aged between 10 and 13 years (M = 14.03 and DT ± 2.15), ofthe 5th and 6th grades of Primary Education who were administered the validated questionnaires Apoyo a lasNecesidades Psicológicas Básicas (CANPB), Cuestionario de motivación en la Educación Física (CMEF) andthe Personal and Social Responsibility. The results showed that the students present a high level of basicpsychological needs, motivation and personal and social responsibility. No significant differences were foundbased on sex for any of the variables analysed. Olders learnes obtained significantly higher values of personalresponsibility and lower levels of identified motivation. Finally, positive and significant relationships were observed between dimensions of motivation, personal and social responsibility and basic psychological needs
Keywords: physical education; education in values; primary education; theory of self-determination